2022
DOI: 10.1186/s13104-022-06040-0
|View full text |Cite
|
Sign up to set email alerts
|

Oroxylin A shows limited antiviral activity towards dengue virus

Abstract: Objective The mosquito transmitted dengue virus (DENV) the causative agent of dengue fever (DF) remains a significant public health burden in many countries. Thailand, along with many countries in Asia and elsewhere, has a long history of using traditional medicines to combat febrile diseases such as DF. Screening bioactive compounds from traditional medicines reported to have antipyretic or anti-inflammatory activity may lead to the development of potent antivirals. In this study oroxylin A (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On the other hand, it was found that compound M78 induces a reduction in NS5 expression, with a dose-dependent effect ( Figure 4 ), and a predicted selectivity index (SI) of 2.5 µM, indicating that the compound is effective and selective at this concentration. This parameter is accepted to express the efficacy of a compound in inhibiting viral replication, although studies have shown that SI values < 10 have limited antiviral activity, as observed in the case of OA, a methylated flavone from Oroxylum indicum , with an SI of 2.66 against DENV-2 [ 53 ]. Furthermore, by using the replicon system, which allows studying aspects of viral replication due to the lack of structural genes [ 30 ], it is possible to consider that the intervention of M78 is directed towards viral replication and/or the expression of proteins associated with this process [ 54 ], which is also evidenced by the reduction in viral RNA copies ( Figure 5 ), where a 2 −ΔΔCT value less than 1 indicates a reduction in gene expression due to the treatment [ 32 ], estimating that such reduction was 1.7 times greater compared to the viral control.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was found that compound M78 induces a reduction in NS5 expression, with a dose-dependent effect ( Figure 4 ), and a predicted selectivity index (SI) of 2.5 µM, indicating that the compound is effective and selective at this concentration. This parameter is accepted to express the efficacy of a compound in inhibiting viral replication, although studies have shown that SI values < 10 have limited antiviral activity, as observed in the case of OA, a methylated flavone from Oroxylum indicum , with an SI of 2.66 against DENV-2 [ 53 ]. Furthermore, by using the replicon system, which allows studying aspects of viral replication due to the lack of structural genes [ 30 ], it is possible to consider that the intervention of M78 is directed towards viral replication and/or the expression of proteins associated with this process [ 54 ], which is also evidenced by the reduction in viral RNA copies ( Figure 5 ), where a 2 −ΔΔCT value less than 1 indicates a reduction in gene expression due to the treatment [ 32 ], estimating that such reduction was 1.7 times greater compared to the viral control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous compounds of natural origin, for instance, flavonoids obtained from various plant sources (quercetin, quercitrin, rutin, oroxylin A), curcumin, alpha-mangostin, mangiferin, etc. have been shown to be active against DENV [ 33 35 ].…”
Section: Anti-dengue Drugsmentioning
confidence: 99%